2022
DOI: 10.1039/d2ta02083a
|View full text |Cite
|
Sign up to set email alerts
|

Alloying electrode coatings towards better magnesium batteries

Abstract: Mastering the metal-electrolyte interface is mandatory for the development of reliable rechargeable magnesium batteries. Nevertheless, most of the current electrolytes contain chlorides species to bypass the surface passivation of magnesium,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…12 Nonetheless, recent research has shown that carbonate-based electrolytes are not ideal for multivalent batteries as the solvent molecules tend to be reduced before the metal deposition can occur. [13][14][15] Promising Ca plating and stripping have recently been reported in electrolytes using glyme-or ether-based solvents, indicating the particular role of low dielectric media in the electrochemical activity of multivalent ions. [16][17][18][19] To design proficient Ca 2+ electrolytes, the solvation structure, the physical properties, and the conduction mechanism in Ca 2+ electrolytes should be well comprehended.…”
Section: Introductionmentioning
confidence: 99%
“…12 Nonetheless, recent research has shown that carbonate-based electrolytes are not ideal for multivalent batteries as the solvent molecules tend to be reduced before the metal deposition can occur. [13][14][15] Promising Ca plating and stripping have recently been reported in electrolytes using glyme-or ether-based solvents, indicating the particular role of low dielectric media in the electrochemical activity of multivalent ions. [16][17][18][19] To design proficient Ca 2+ electrolytes, the solvation structure, the physical properties, and the conduction mechanism in Ca 2+ electrolytes should be well comprehended.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate such an underneath plating mechanism, we computed the underneath plating energy (UPE, already introduced and detailed in ref. 36 and 55) which corresponds to the energy cost for Li atoms to plate in a new Li bulk phase, i.e. , in between the Ni foam and the protective layer.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate such an underneath plating mechanism, we computed the underneath plating energy (UPE, already introduced and detailed in refs. 36,55 ) which corresponds to the energy cost for Li atoms to plate in a new Li bulk phase, i.e., in between the Ni foam and the protective layer 36,55 . If the UPE is negative, it is thermodynamically more favorable for the Li atoms plate underneath rather than staying on top of the coating.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] Recently, the use of liquid gallium was proposed to protect the surface of magnesium electrodes. [14,15] Taking advantage of the low melting point of gallium, it is possible to spread droplets on the surface of the magnesium electrodes. The subsequent chemical reaction leads to the formation of a top layer mainly composed of crystalline Mg 2 Ga 5 , and enhanced cycling behavior was achieved with these as-protected electrodes in magnesium bis(trifluoromethanesulfonyl)imide (Mg(TFSI) 2 )/dimethoxyethane (DME).…”
Section: Introductionmentioning
confidence: 99%